Біологічна активність екзометаболітів ароматичних рослин та перспективи їх використання в агрофітоценології - Radiosa, S.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
The author present the literary data about the exometabolites of aromatic plants. It have been shown the meaning in allelopathy and perspectives of their use. The actuality of researches of Calendula genus species at the aspect of agrophytocenology is demonstrated.